Questions regarding the Development of Territorial Law - Valle Videla, Luz (Cuadernos de Historia del Derecho, 2018)
Galo Sánchez was the first scholar to seriously examine early compilations of Castilian territorial law. Since his study «Para la historia de la redacción del antiguo derecho territorial castellano», it is widely acknowledged that these collections are unpolished, rudimentary legal compilations, as evidenced by the fact that they contain numerous chapters repeating the same laws. Amongst the various collections, the Fuero viejo de Castiella is seen as an exception, since it contains texts of a more general character. Part of Galo Sánchez’s hypothesis lays on the fact of fueros displaying anecdotal details. However, when these fueros are analyzed, it becomes clear that the redactors include anecdotal details for specific reasons, as we intend to demonstrate here. This study will examine the aims of the compilers of the Libro de los fueros de Castilla and the Fuero viejo when introducing concrete details into the abstract discourse of the fueros. We will further argue that these fueros did not evolve out of ancient fazañas.
Keywords: elaboration of territorial law; anecdotic fueros; fazañas.